2012
DOI: 10.1002/app.36732
|View full text |Cite
|
Sign up to set email alerts
|

Effects of compatibilizers on the mechanical properties of ABS/PLA composites

Abstract: Composites composed of acrylonitrile‐butadiene‐styrene copolymer (ABS) and poly(lactic acid) were prepared to develop ABS‐based automobile console boxes with improved environmental friendliness. ABS/PLA composites without any additives showed extremely poor mechanical properties. However, increase in the content of polybutadiene moiety of ABS and introduction of proper compatibilizer and heat stabilizer enhanced the mechanical properties of ABS/PLA composites significantly. Thermal stabilization effect of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 19 publications
(17 reference statements)
2
37
0
Order By: Relevance
“…The results showed that SAN-g-MAH was the most effective compatibilizer [35]. Wang et al [36] also used PC to toughen PLA.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The results showed that SAN-g-MAH was the most effective compatibilizer [35]. Wang et al [36] also used PC to toughen PLA.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…As a biodegradable thermoplastic, poly(lactic acid) (PLA), derived from starches and sugars, has attracted much attention from industry and academia . Its applications have extended from initial packaging materials to the electronics, automobiles, and other fields . So it is necessary and urgent to improve its combustion behavior.…”
Section: Introductionmentioning
confidence: 99%
“…used SAN‐GMA at 20 wt % loading along with a heat stabilizer to increase the toughness to 158 J/m. They concluded that the high rubber content ABS and the heat stabilizer enhanced the dispersion to increase the impact strength . Dong et al .…”
Section: Introductionmentioning
confidence: 99%